Isthmus connecting mainland and island of stability of superheavy nuclei; Physical Review C; Vol. 106, iss. 1 - Hong Juhee; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Kowal M. Michal; Jachimowicz P. Piotr (2022, 2022)
Title screen